Effect of hot-pressing sintering temperature and pressure on the densification and properties of Ti-TiB composites - Padiri Murali; Kausik Chattopadhyay; Vikas Jindal (Journal of Alloys and Metallurgical Systems)
Ti/TiB composites exhibit promising potential for applications in the automotive, aerospace, and biomedical sectors. Hot pressing coupled with in situ reaction synthesis is a commonly employed technique for fabricating discontinuously TiB-reinforced titanium matrix composites. Despite its efficacy, comprehensive research investigating the influence of hot-pressing process parameters on the densification and properties of these composites remains scarce. This study systematically examined the effects of pressure (16–48 MPa) and temperature (1250 °C to 1350 °C) on the density, microstructure, and mechanical properties of Ti/TiB composites produced through hot pressing. By analyzing densification curves and rate curves, the densification behavior under varying processing conditions was elucidated. The results indicate that elevated sintering temperatures and pressures correlate with increased densification rates, reduced porosity, and enhanced sample density. A strong relationship between relative densities and hardness was observed. This research contributes to a deeper understanding of the hot-pressing sintering process for Ti-TiB composites and facilitates the optimization of processing conditions.